Struvite recovered from various types of wastewaters: Characteristics, soil leaching behaviour, and plant growth. (19th June 2018) - Ahmed, Naveed; Shim, Soomin; Won, Seunggun; Ra, Changsix
Abstract: Phosphorus (P) is a nonrenewable resource that can be recycled from high nutrient (N and P)‐containing wastewaters as struvite that has 5.7% N and 12.5% P, has lower heavy metal content, is sparingly soluble in water, is highly soluble in organic acids, is devoid of pathogens, is non‐toxic, and can leach nutrients very slowly for longer periods compared with highly soluble mineral fertilizers that leach nutrients very quickly. Leaching of nutrients from struvite can be enhanced by soil nitrification rates, powdered form, and mixing with soil, whereas leaching can be decreased by application on soil surface and granulation. Several plants such as maize, lettuce, ryegrass, and wheat were successfully grown using struvite with higher, comparable, or lesser growth and P uptake compared with commercial fertilizers. High growth and P uptake was synergistically complemented due to high Mg concentrations. As a whole, struvite can be a sustainable and renewable alternative to the mineral fertilizers.